Molecular and serological detection of Babesia bovis- and Babesia bigemina-infection in bovines and water buffaloes raised jointly in an endemic field - Romero-Salas, Dora (2016)
Babesia bovis and Babesia bigemina are causative agents of bovine babesiosis, a tick-borne disease of cattle in tropical and subtropical regions. Babesia spp. infection adversely affects cattle health and can be fatal resulting in considerable economic loss worldwide. Under endemic stability conditions, herds contain high numbers of chronically infected, asymptomatic carrier animals, in which no parasitemia is detected by microscopic blood smear examination. In addition to bovines, also water buffaloes are infected by both Babesia spp. commonly leading to a subclinical infection. The infection rate (by nPCR) and herd exposure (by IFAT) of bovines and water buffaloes reared under similar field conditions in an area of endemic stability were determined and compared. In order to optimize direct parasite detection, highly sensitive nPCR assays were developed and applied, allowing the detection of as little as 0.1 fg DNA of each Babesia pathogen. Significantly lower percentages (p < 0.001) of seropositive water buffaloes compared to bovines were observed for B. bovis (71.4% vs. 98%) and B. bigemina (85% vs. 100%). Interestingly, in comparison, differences noticed between water buffaloes and bovines were considerably larger with direct parasite detection by nPCR (16.2% vs. 82.3% and 24% vs. 94.1% for B. bovis and B. bigemina, respectively). As expected, bovines subjected to monthly acaricide applications exhibited a significant lower infection rate as determined by nPCR than bovines not subjected to these measures (B. bovis 33.3% vs. 90.7%, p < 0.001; B. bigemina 80% vs. 96.5%, p < 0.001, for treated vs. untreated animals). Interestingly no differences between these groups were observed with respect to seropositivity, suggesting similar rates of parasite exposure (B. bovis 100% vs. 97.7%, p < 0.001; B. bigemina 100% vs. 100%, p < 0.001). Importantly, a significantly higher number of water buffaloes as determined by nPCR were infected when reared jointly with bovines not subjected to tick control than when reared jointly with bovines subjected to tick control (B. bovis 31.6% vs. 9.5%, p < 0.01; B. bigemina 42.1% vs. 9.5%, p < 0.01, for water buffaloes reared with untreated vs. treated bovines) and/or when reared without bovines (B. bovis 31.6% vs. 11.6%, p < 0.01; B. bigemina 42.1% vs. 20%, p < 0.01). An accumulation of seropositivity and a decline of infection rates were observed in older animals, while differences observed with regard to gender may warrant further investigation. In summary, our findings suggest that water buffaloes are much more capable to limit or eliminate Babesia infection, possibly due to a more capable immune defense. Furthermore, an increased Babesia spp. parasite reservoir of bovines seems to increase the infection rate of water buffaloes when both are reared on the same pasture.